MODEL PEMILIHAN RUTE BUS JAYA UTAMA DAN BUS SUGENG RAHAYU DENGAN MENGGUNAKAN METODE PEMBEBANAN BERTAHAP (STUDI KASUS: TERMINAL PURABAYA - TERMINAL TERBOYO) - Fauzan Rokhimi; Nugroho Utomo; Ibnu Sholichin (Journal of Civil Engineering Science and Technology (CI-TECH), 2022)
Pattern of interaction that occurs between the City of Surabaya and the City of Semarang is not only limited to economic factors but more than that the pattern of interaction takes place in all aspects of human life. People who are outside the Semarang City area will try to choose the fastest route from several routes that connect between the zones of origin to Semarang City. This research was conducted based on the factors that influence the process of selecting travel routes from the city of Surabaya to the city of Semarang using the inter-city inter-provincial bus (AKAP) public transportation. This study uses a gradual loading method because this method can be used to determine the relationship between traffic flow and vehicle travel time, not depending on the assumptions of road users and the characteristics of the road network. The results of simple linear regression analysis, obtained a flow-cost relationship model on route A (Terminal Purabaya - Nganjuk - Ngawi - Solo - Ungaran - Terminal Terboyo) the form of the equation is YA = 48.937 + 0.022X. While the flow-cost relationship model on route B (Terminal Purabaya - Gresik - Lamongan - Tuban - Rembang - Kudus - Terminal Terboyo) the form of the equation is YB = 36,822 + 0.034X. The coefficient of determination (R2) on route A is 0.6 and on route B the result is 0.4. The final result of loading the travel route with a uniform loading fraction of 5% obtained a Wardrop balance convergence value of 0.003. Keywords: simple linear regression analysis, stepwise loading method, travel route selection.